Training and innovation - Bauernschuster, Stefan [Verfasser]; Falck, Oliver [Verfasser]; Heblich, Stephan [Verfasser] (My University, 2009)
"Research analyzing the importance of human capital for innovation usually focuses on secondary and tertiary education. This paper takes a different perspective by focusing on in-firm training. We argue that continuous training guarantees access to leading-edge knowledge and thus increases a firm's propensity to innovate. Using German establishment-level data, we show a strong association between lagged continuous training and innovation. Applying instrumental variable methods, we cautiously argue that the association between training and innovation is indeed a causal effect. In the quest for a relevant and valid instrument, we exploit legal regulations of the German Works Constitution Act." (Autorenreferat, BIBB-Doku)
Keywords: S 1.5.3 Betriebliche Weiterbildung; S 4.3.6 Human Capital; Betriebliche Weiterbildung; Humankapital; Innovationsfähigkeit; Arbeitsproduktivität; Betriebsverfassungsgesetz